MANAGEMENT INFORMATION SYSTEM AS A SUPPORT BUSINESS STRATEGY IN THE DIGITAL ERA - Rizki Zaskiyah Daulay; Elke Dwi Soraya; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
In this digital age, Management Information Systems (MIS) play a crucial role in underpinning business strategy. This research examines how MIS integrates people, technology, and organization to improve decision-making, work efficiency, and competitive advantage. By turning raw data into useful insights, MIS helps companies maximize performance, cut costs, and respond to market changes immediately. The research emphasizes the importance of a flexible and adaptable MIS structure to keep pace with advances in digital technology and the dynamic business world. In essence, the proper use of MIS not only supports day-to-day activities but also drives critical decisions that keep businesses thriving and competitive in the digital age. In the current age of globalization, the importance of management information systems (MIS) in promoting effective business operations and supporting sound decision-making is vital. This article examines how the implementation of SIM allows companies to incorporate information technology, enhance productivity, manage data efficiently, and quickly adapt to changes in the market. Nonetheless, the execution of SIM involves more than just technology alone. This article also emphasizes the significance of company culture and the enhancement of employees' digital skills in facilitating adaptation to swift technological advances.